Effect of sulfidation on ethaline-assisted electrodeposited iron sulfide-based electrocatalyst for efficient saline water splitting - Mottakin M.; Su'ait M.S.; Selvanathan V.; Chelvanathan P.; Ibrahim M.A.; Akhtaruzzaman M. (Elsevier Ltd, 2025)
This study investigated the synthesis of ethaline-assisted iron sulfide on nickel foam (NF) using the electrodeposition method to facilitate saline water splitting. The oxidization of iron and the formation of Fe(OH)3 on the cathode surface pose challenges for the electrodeposition of iron sulfide from aqueous solutions. To tackle these issues, deep eutectic solvent-assisted electrodeposition and ethaline-assisted sulfidation methods have been investigated for synthesizing FeS2. These approaches aim to enhance the efficiency of the iron sulfide electrode by preventing unwanted oxidation and ensuring the formation of high-quality coatings. Sulfidation in non-aqueous media was performed at varying durations, revealing that sulfur content significantly impacts the morphology of the prepared electrode. The optimum FeS2/NF catalyst offers the lowest overpotential of 194 mV at 10 mA cm?2 for oxygen evolution reaction (OER) and 176 mV at 10 mA cm?2 for hydrogen evolution reaction (HER) in saline water splitting. The enhanced catalytic activity is attributed to the formation of multiphasic components in the catalyst. The electrodes exhibited stability in saline water conditions for approximately 10 h for both OER and HER. Moreover, FeS2/NF exhibited stability for 50 h in OER and 20 h in HER when applied to pure water splitting. The investigation explores the unique synthesis of FeS2 in non-aqueous media and examines its catalytic activity in saline water electrolysis. ? 2024 Hydrogen Energy Publications LLC